VARIASI BAHASA KOMUNIKASI GURU DAN SISWA BERBASIS WHATSAPP GROUP DI SMP NEGERI 4 PEKALONGAN - Armanda Miladia; Erwan Kustriyono (STKIP Subang, 2026)
This study aims to describe the language variations used by teachers and students in communication through WhatsApp Groups at SMP Negeri 4 Pekalongan, identify the factors influencing their occurrence, and examine their implementation in Indonesian language learning. This research employed a qualitative descriptive approach, with data sources consisting of conversations between teachers and students in the WhatsApp Groups of Grade VII and Grade VIII classes. The data were collected through observation, documentation, and note-taking techniques, and then analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings reveal that language variation based on the level of formality includes the Formal Style, Consultative Style, and Casual Style, while the Frozen Style and Intimate Style were not found. The emergence of these language variations is influenced by communication situations, teacherstudent relationships, the use of WhatsApp as a communication medium, speakers' age, communication efficiency, and social media usage habits. The study also demonstrates that WhatsApp Group conversations can be utilized as authentic teaching materials in teaching procedural texts for Grade VII and Grade VIII Indonesian language classes. This research contributes to the field of sociolinguistics while offering an alternative source of contextual and relevant teaching materials that reflect students' digital communication practices.